Adsorption kinetics of dye wastewater in aqueous solution by activated carbon from capsicum straw. (2016) - Qiu, Muqing; Xiong, Shuiying; Lin, Jianbo
The presence of these coloured compounds in wastewater is not only aesthetically displeasing but also they impede light penetration in the treatment pans, thus upsetting the biological treatment processes within the treatment plant. Therefore, it is necessary to reduce dye concentration in the wastewater. Activated carbon was obtained from capsicum straw by chemical activation using KOH as an activator. Then, it was used as an adsorbent for the removal of dye wastewater from aqueous solution. The adsorption of dye wastewater in aqueous solution by activated carbon from capsicum straw was carried out. The effect of contact time, concentration of dye wastewater from aqueous solution and temperature was researched. The experimental data were analysed by the Langmuir and Freundlich models of adsorption. Kinetic adsorption data were analysed by the pseudo-first-order kinetic model, the pseudo-second-order model and the intraparticle diffusion model respectively. The thermodynamics parameters were also calculated. From these results of adsorption process of dye wastewater from aqueous solution by the activated carbon, the activated carbon was found to be both effective and economical.